Emergent Catalytic Behavior of Self‐Assembled Low Molecular Weight Peptide‐Based Aggregates and Hydrogels. Issue 19 (23rd March 2016) - Tena‐Solsona, Marta; Nanda, Jayanta; Díaz‐Oltra, Santiago; Chotera, Agata; Ashkenasy, Gonen; Escuder, Beatriu
Abstract: We report a series of short peptides possessing the sequence (FE) n or (EF) n and bearingl ‐proline at their N‐terminus that self‐assemble into high aspect ratio aggregates and hydrogels. We show that these aggregates are able to catalyze the aldol reaction, whereas non‐aggregated analogues are catalytically inactive. We have undertaken an analysis of the results, considering the accessibility of catalytic sites, p K a value shifts, and the presence of hydrophobic pockets. We conclude that the presence of hydrophobic regions is indeed relevant for substrate solubilization, but that the active site accessibility is the key factor for the observed differences in reaction rates. The results presented here provide an example of the emergence of a new chemical property caused by self‐assembly, and support the relevant role played by self‐assembled peptides in prebiotic scenarios. In this sense, the reported systems can be seen as primitive aldolase I mimics, and have been successfully tested for the synthesis of simple carbohydrate precursors. Abstract : Primitive aldolase I mimics : Short self‐assembled peptides show emergent catalytic behavior for direct aldol reactions (see figure). The accessibility of catalytic sites, p K a value shifts, and the presence of hydrophobic pockets were also analyzed.